DESIGNING OF MODULAR PROFESSIONAL EDUCATION STUDY PROGRAMME IN COMPETENCE-BASED MODEL - Jankovska, Līvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Competence based education is widely discussed for the development of vocational and professional schools. The main goal of professional training is to prepare students for successful integration in professional and social life. Competence approach is considered to have a good potential to transform and improve professional study process. The aim of this paper is to study designing of competence based professional curriculum in regard to making cuuriculum structure, models and principles. Theoretical study of the competence based approach in education, planning and creating of modular and result -oriented course programmes was made. The aims, strategies, factors, and stages for contemporary learning programme are investigated. Then the concepts and structures are analysed. The results of the research show that designing competence-based curriculum is complicated, creative and innovative process. There are a lot of factors which should be taken into consideration,such as a competence as an organizational element of the curriculum.National education and professional standards make the basis to define the aims and variety of competences. Constructural, human and holistic education theories determine main principles and content of the curriculum.